Doped Framework Iron Hydroxyl Phosphate as Photocatalyst for Hydrogen Production from Water/Methanol Mixtures. Issue 25 (September 2015) - Serra, Marco; Baldovi, Herme G.; Alvaro, Mercedes; Garcia, Hermenegildo
Abstract: In the search for novel photocatalysts for hydrogen production and with the α‐Fe2 O3 photoelectrocatalyst as a recent precedent, we report herein the preparation, semiconductor properties and photocatalytic activity of metal‐doped (0.1–5 wt.‐% loading) iron hydroxyl phosphate (FeP). X‐ray diffraction analyses of FeP samples subjected to extended photocatalytic irradiation showed the stability of this framework phosphate under photocatalytic conditions. Doping increased the photocatalytic efficiency of FeP for all dopants, with the optimal doping level between 0.1 and 1 %. Under the optimized conditions (Cr at 1 % doping), the photocatalytic activity of FeP reached a hydrogen production rate of 35.82 μmol gFe –1 in the absence of platinum as co‐catalyst. The conduction flat band potential was estimated by photocurrent measurements or impedance spectroscopy to be 0.1 eV versus NHE and the charge carrier density 2.6 × 10 20 carriers cm –3 . Transient absorption spectroscopy revealed a transient species decaying on the microsecond timescale characterized by a broad band spanning 300–750 nm. This transient was attributed to the charge‐separated state. These results are promising for the development of novel photocatalytic materials based on framework metal phosphate. Abstract : Open‐framework iron hydroxyl phosphate can be easily doped and exhibits semiconductor behaviour under visible light leading to hydrogen generation